EFFECT OF PROBIOTICS ON ZONULIN LEVELS AND INTESTINAL MICROBIOTA COMPOSITION IN FUNCTIONAL GASTROINTESTINAL DISORDERS (Multidisciplinary Journal of Science and Technology, 2026)
Functional gastrointestinal disorders (FGIDs) are among the most prevalent chronic conditions in gastroenterological practice and are characterized by persistent gastrointestinal symptoms in the absence of identifiable structural pathology. Increasing evidence indicates that impaired intestinal barrier function and alterations in gut microbiota composition play a central role in the pathogenesis of FGIDs. Zonulin, a key regulator of intestinal tight junctions, serves as a biomarker of increased intestinal permeability and is frequently elevated in patients with FGIDs.This study was conducted at the Khorezm regional multidisciplinary medical center and aimed to evaluate the effect of probiotic therapy on serum zonulin levels and intestinal microbiota composition in patients with functional gastrointestinal disorders. Patients were stratified into study groups based on treatment modality. The results demonstrate that probiotic supplementation significantly reduces zonulin levels, improves gut microbiota balance, and alleviates clinical symptoms, confirming the role of probiotics as an effective adjunct in FGID management.